DESCRIPTIVE ANALYSIS OF SUSTAINABLE BUSINESS IN NEARBY SHARIA HOTEL SUBANG - Mutqi Sopiawadi; Bismantara Bismantara; Wisnu Saputra (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
The sharia hotel business continues to grow in Indonesia, with increasing demand from Muslim tourists seeking tourism experiences that align with their religious values. Sustainability is an important aspect of the sharia hotel business, because Islam teaches Muslims to be responsible stewards of the earth. This research aims to analyze the current conditions of the sustainability business in sharia hotels in Indonesia. Descriptive analysis is used to describe the sustainability practices implemented by sharia hotels, such as energy use, water management, waste reduction, and social responsibility. Data was collected through in-depth interviews with sharia hotel managers. The data was analyzed using descriptive qualitative. The research results showed that sharia hotels in Indonesia generally implement sustainable practices. However, there is still room for improvement, especially in terms of energy use and water management. Sharia hotels also need to improve communication about their commitment to sustainability to guests and other stakeholders. The sustainability business is an important opportunity for sharia hotels in Indonesia. By implementing sustainable practices, sharia hotels can improve their image, attract more guests, and contribute to environmental conservation.